The effects of drug-sensitive and drug-resistant Trypanosoma congolense infections on the pharmacokinetics of homidium in Boran cattle - Murilla, G.A.; Peregrine, A.S.; Ndung'u, J.M.; Holmes, P.H.; Eisler, M.C. (Elsevier, 2002)
Two groups of five Boran (Bos indicus) cattle were infected with one of two populations of Trypanosoma congolense; one drug-sensitive (IL1180), and one drug-resistant (IL3330). The animals were then treated intramuscularly with homidium bromide at a dose rate of 1.0 mg kg - bodyweight 7 days after trypanosomes were detected in the peripheral blood of all the five animals in each grouFollowing treatment of cattle infected with drug-sensitive trypanosomes. parasites could no longer be detected in the bloodstream of four out of five cattle after 24 h, and after 48 h for the fifth animal. The animals remained aparasitaemic up to the end of the observation period of 90 days and serum drug concentrations determined by enzyme-linked immunosorbent assay (ELISA) remained above the detection limit of 0.1 ng ml for the entire period. Following treatment of cattle infected with drug-resistant trypanosomes. parasites did not disappear from the bloodstream in any of the five animals. The rate of drug elimination was greater in cattle infected with drug-resistant trypanosomes and the drug was no longer detectable approximately 3 weeks after treatment. Non-compartmental pharmacokinetic analysis showed that the values for t1 beta, of 75.5 ± 16.9 h, the area under the curve (AUC a-x ) of 1.33 ± 0.156 mce g h ml - and the MRT a-x of 32.8 ± 4.45 h obtained in cattle infected with the drug-resistant trypanosome population were significantly lower than the values of 424 ± 146 h for tJl, 1.67 ± 0.233 mug h ml -1 for AUC a-x and 297 ± 159 h for MRT a-x obtained in cattle infected with the drug sensitive population. The persistence of drug-resistant infections in cattle following homidium treatment was associated with more rapid drug elimination than in those in which infections with drug-sensitive parasites were cleared by the drug.